Molecular Characteristics and Zoonotic Potential of Salmonella Weltevreden From Cultured Shrimp and Tilapia in Vietnam and China - Hounmanou, Yaovi M. G.; Dalsgaard, Anders; Sopacua, Tirzania Frannetta; Uddin, Gazi Md. Noor; Leekitcharoenphon, Pimlapas; Hendriksen, Rene S.; Olsen, John E.; Larsen, Marianne Halberg (Frontiers in Microbiology, 2020)
Salmonella Weltevreden is increasingly reported from aquatic environments, seafood and patients in several Southeast Asian countries. Using genome-wide analysis, we characterized S. Weltevreden isolated from cultured shrimp and tilapia from Vietnam and China to study their genetic characteristics and relatedness to clinical isolates of S. Weltevreden ST-365. The phylogenetic analysis revealed up to 312 SNPs difference between tilapia isolates, while isolates from shrimp were genetically more closely related. Epidemiologically unrelated isolates from Vietnam were closely related to isolates from China, e.g. 20 SNPs differences between strains 28V and 75C. In comparison with strains from other parts of the world, our environmental isolates predominantly clustered within the continental South Asia lineage, constituted mostly of strains from human stool with as low as seven SNPs difference, e.g. 30V vs Cont_ERR495254. All sequenced isolates were MLST type ST-365 and contained the major virulence-related genes encoded by the Salmonella Pathogenicity Islands 1 to 5. Ten of the isolates harbored the IncFII(S) plasmid similar to the virulence genes-mediated plasmid pSPCV of S. Paratyphi C, and one isolate had the IncQ1 plasmid on the same contig with strA/B, sul2 and tetA resistance genes similar to the IncQ1 type, pNUC of S. Typhimurium. A pangenomic analysis yielded 7,891 genes including a core-genome of 4,892 genes, with a closely related accessory genome content between clinical and environmental isolates (Benjamini p>0.05). In a search for differences that could explain the higher prevalence of S. Weltevreden in aquatic samples, genomes were compared with those of other Salmonella enterica serovars. S. Weltevreden revealed specific regions harboring glpX (Fructose-1;6-bisphosphatase; class II), rfbC (dTDP-4-dehydrorhamnose 3;5-epimerase) and cmtB (PTS Mannitol-specific cryptic phosphotransferase enzyme IIA component) involved in carbohydrate biosynthesis pathways. Our study builds grounds for future experiments to determine genes or pathways that are essential when S. Weltevreden are in aquatic environments and microbial interactions providing survival advantages to S. Weltevreden in such environments.